Hazardous drinking and its association with homelessness among veterans in care - Ghose, T. (Drug Alcohol Depend, 2013)
BACKGROUND: While scholarship on alcohol use and homelessness has focused on the impact of alcohol abuse and dependence, little is known about the effects of lower levels of misuse such as hazardous use. Veterans receiving care in the Department of Veterans Affairs Health Care System (VA) constitute a population that is vulnerable to alcohol misuse and homelessness. This research examines the effects of hazardous drinking on homelessness in the Veterans Aging Cohort Study, a sample of 2,898 older veterans (mean age=50.2), receiving care in 8 VAs across the country. METHODS: Logistic regression models examined the associations between (1) hazardous drinking at baseline and homelessness at 1-year follow-up, (2) transitions into and out of hazardous drinking from baseline to follow-up and homelessness at follow-up, and (3) transitioning to hazardous drinking and transitioning to homelessness from baseline to follow-up during that same time-period. RESULTS: After controlling for other correlates including alcohol dependence, hazardous drinking at baseline increased the risk of homelessness at follow-up (adjusted odds ratio [AOR]=1.39, 95% confidence interval [CI]=1.02, 1.88). Transitioning to hazardous drinking more than doubled the risk of homelessness at follow-up (AOR=2.42, 95% CI=1.41, 4.15), while more than doubling the risk of transitioning from being housed at baseline to being homeless at follow-up (AOR=2.49, 95% CI=1.30, 4.79). CONCLUSIONS: Early intervention that seeks to prevent transitioning into hazardous drinking could increase housing stability among veterans. Brief interventions which have been shown to be effective at lower levels of alcohol use should be implemented with veterans in VA care.